Multiple dinosaur egg-shell occurrence in an Upper Cretaceous nesting site from Patagonia - Coria, Rodolfo Anibal (2010)
Fil: Coria, Rodolfo A. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.